Dielectric and Magnetic Studies La+3 doped Cobalt Nano Ferrite. Issue 1 (July 2021) - Ragini, N.; Ayesha, Syeda; P Komal, K.; Fatima, Tanveer; Harsha, G. A; Shilpa, S; Abdul Khader, S.
Abstract: La 3+ substituted cobalt ferrite nano-particles with the chemical composition Lax CoFe2-x O4 (here, x=0, 0.05, 0.1, 0.15 and 0.2) were synthesized using auto-combustion method. Structural and morphological studies were probed using X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM). Formation of rare-earth doped cobalt ferrite was confirmed using the X-ray diffraction studies. Average crystallite size (D) was found to be varying from 43.71nm to 55.37nm with the increase in La 3+ concentration. Frequency dependent dielectric properties of synthesized samples were measured from 100 Hz to 1 MHz at room temperature using a precision HIOKI make LCR HI-TESTER. Dielectric dispersion was observed at lower frequencies for the synthesized samples. Magnetic properties were studies using Vibrating Sample Magnetometer (VSM), all the synthesized samples exhibited well defined magnetic hysteresis curves, there by confirming the magnetic behaviour of the sintered samples.